Information security management metrics in web application - Abd. Rahim, Mohd. Hafiz (2013)
Nowadays web application becomes an important part of every one’s life to pay bills online, to buy things online and so many more. Despite the rapid growth of web application based software, the vulnerabilities of web application and the attacks also increase rapidly too. Many web developers ignore the importance of developing web application with security in their mind. As a result, many hackers even script kiddies could gain or steal web application user’s sensitive data such as credit card number, user ID and password and so on for their own evil deeds. To evaluate the information security management metrics in web application, the researcher used questionnaire method. The respondents are web application programmer from different level such as experienced, intermediate and novice level. To help developer build web application with security in mind is to create a matrix mapping of information security management metrics in web application to raise awareness of web application vulnerabilities during the web application development. This way, it could help developer to not only raise their awareness regarding security of building a web application, moreover it could help diminished cost of fixing bugs that are found during software development life cycle phase (SDLC).